Antimicrobial and ADME properties of methoxylated, methylated and nitrated 2-hydroxynaphthalene-1 carboxanilides - Lucia Vrablova; Tomas Gonec; Tereza Kauerova; Michal Oravec; Izabela Jendrzejewska; Peter Kollar; Alois Cizek; Josef Jampilek (ADMET and DMPK)
Background and purpose: Many new compounds are being prepared to overcome the problem of increasing microbial resistance and the increasing number of infections. Experimental approach: This study includes a series of twenty-seven mono-, di- and trisubstituted 2-hydroxynaphthalene-1-carboxanilides designed as multitarget agents. The compounds are substituted with methoxy, methyl, and nitro groups, as well as additionally with chlorine, bromine, and trifluoromethyl at various positions. All the compounds were evaluated for antibacterial activities against Gram-positive and Gram-negative bacteria and mycobacteria. Cytotoxicity on human cells was also tested. Key results: Three compounds showed activity comparable to clinically used drugs. N-(3,5-Dimethylphenyl)-2-hydroxynaphthalene-1-carboxamide (13) showed only anti¬sta¬phylococcal activity (minimum inhibitory concentration (MIC) = 54.9 µM); 2-hydroxy-N-[2-methyl-5-(tri¬fluoro¬methyl)phenyl]naphthalene-1-carboxamide (22) and 2-hydroxy-N-[4-nitro-3-(trifluoromethyl)phe¬nyl]na¬phtha¬lene-1-carboxamide (27) were active across the entire spectrum of tested bacteria/mycobacteria, both against the sensitive set and against resistant isolates (MICs range 0.3 to 92.6 µM). Compound 22 was even active against E. coli (MIC = 23.2 µM). The active agents showed no in vitro cytotoxicity up to a concentration of 30 μM. Conclusion: Compounds with trifluoromethyl in the meta-anilide position, experimental lipophilicity expressed as log k (logarithm of the capacity factor) in the range of 0.31 to 0.34 and calculated electron σ parameter for the anilide substituent higher than 0.59 were effective. The investigated compounds meet the definition of Michael acceptors. Based on ADME screening, the investigated compounds 13, 22 and 27 should have suitable physico¬chemical parameters for good bioavailability in the organism. Therefore, these are promising agents for further study.